Development of VR-Based Learning Media for the Buya Hamka Birth Museum to Increase Motivation to Learn History in Class XI of Muhammadiyah 1 Vocational School, Pekanbaru - Murni, Ildri Maysah; Ahmal, Ahmal; Al Fiqri, Yanuar (FKIP - Universitas Riau, 2025)
This study aims to develop Virtual Reality (VR)-based learning media at the Buya Hamka Birth Museum to enhance students' motivation in learning history. The research was conducted at SMK Muhammadiyah 1 Pekanbaru, focusing on the history subject for Grade XI students. The background of this study arises from students' lack of interest in history lessons due to conventional teaching methods that rely heavily on textbooks. To address this issue, the research develops an interactive VR learning medium that allows students to explore historical sites virtually. The research follows the Research and Development (R&D) method using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection involved observations, interviews, and questionnaires distributed to students and history teachers. The VR-based learning media was validated by experts in both media and historical content before being tested in small and large groups of students. The findings indicate that the VR learning media is effective in increasing students' motivation and engagement in history lessons. Students showed a higher level of enthusiasm and understanding when using VR compared to traditional learning methods. In conclusion, VR-based learning media can be an innovative solution to make history lessons more immersive and appealing.